What is the Functional Difference Between Sagittal With Metopic and Isolated Sagittal Craniosynotosis?. Issue 4 (June 2019) - Cabrejo, Raysa; Lacadie, Cheryl; Chuang, Carolyn; Yang, Jenny; Sun, Alexander; Brooks, Eric; Beckett, Joel; Eilbott, Jeffrey; Gabrick, Kyle; Steinbacher, Derek; Alperovich, Michael; Pelphrey, Kevin; et al.
Abstract : Introduction: The purpose of this study is to understand the neurological differences between patients born with combined sagittal and metopic craniosynostosis (SMc) and isolated sagittal craniosynostosis (ISc) by studying aberrations in functional brain connectivity and white matter microstructure, before surgery, utilizing functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI). Methods: The authors collected DTI and resting-state (ie, no sedation and asleep) functional connectivity MRI data in 10 infant patients preoperatively: 5 in the SMc group (4.3 ± 1 months) and 5 in the ISc group (4.8 ± 1.1 months). Resting state fMRI imaging and DTI data were acquired using a 3-T Siemens Trio MRI system (Erlangen, Germany) while the infant patients slept. fMRI data were corrected for movement using SPM, underwent cerebrospinal fluid and white matter signal regression and further analyzed with BioImageSuite. For the DTI data, 3 diffusion runs were averaged, processed utilizing FMRIB Software Library, and analyzed statistically using BioImageSuite. Results: Comparing the SMc versus ISc groups, SMc demonstrated that there was increased connectivity, statistically significant differences, in neural networks between children with sagittal synostosis alone versus those with sagittal with metopic synostosis, in the right BA 31 and BA 23 (corresponding to the posterior cingulate cortex (PCC) ( P < 0.001). Analysis of the DTI revealed increased fractional anisotropy (normal maturation of white tracts) in the SMc group in the cingulum compared to the ISc group ( P < 0.05). Differences in the functional networks include increased connectivity right frontoparietal network (RFPN) in ISc and increased connectivity in the primary visual network (V1) in SMc ( P < 0.001). Conclusion: The SMc had increased connectivity as measured by fMR in the PCC, an area associated with attention deficit hyperactivity disorder. The DTI analysis demonstrated an increase in fractional anisotropy of the cingulum in the SMc group, a white matter tract projecting from the cingulate cortex; connections of the limbic (emotional regulation) system are instrumental. In SMc, increase of connectivity in the PCC correlates with an increase in maturation of the cingulum compared to ISc. There is increased connectivity of the RFPN network in the ISc and increased connectivity of the V1 network in the SMc patients. The SMc group has increased connectivity in the PCC, the original seed of the DMN network, and decreased connectivity to the RFPN network. The pattern of increased connectivity in the area of the DMN and decreased connectivity in the RFPN network is similar to the trend when comparing ADHD patients to normal controls. SMc has more similar functional network connectivity to ADHD as compared to ISc.